2000
DOI: 10.1590/s0100-40422000000100013
|View full text |Cite
|
Sign up to set email alerts
|

Corantes têxteis

Abstract: Recebido em 7/10/98; aceito em 31/3/99 TEXTILE DYES. A dye is a colored substance used to impart permanent color to other substances. Its most important use is in coloring textile fibers and fabrics. The removal of colour from dyehouse waste waters is currently a major problem in the textile sector. This paper provides an overview of the treatment technologies that can currently be used by the textile processor and the developments over the past decade with respect to the toxicological and ecotoxicological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
90
0
99

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(190 citation statements)
references
References 11 publications
1
90
0
99
Order By: Relevance
“…There are around 10,000 different industrial dyes and pigments, totaling an annual world consumption of 700,000 tons (Pearce et al, 2003), 26,500 tons of which are consumed in Brazil (Guaratini and Zanoni, 2000). Reactive Blue 5G is one of the main dyes used in dyeing facilities since it is used in the production of blue denim.…”
Section: Introductionmentioning
confidence: 99%
“…There are around 10,000 different industrial dyes and pigments, totaling an annual world consumption of 700,000 tons (Pearce et al, 2003), 26,500 tons of which are consumed in Brazil (Guaratini and Zanoni, 2000). Reactive Blue 5G is one of the main dyes used in dyeing facilities since it is used in the production of blue denim.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, an increasing concern, regarding the high concentrations of dyes in effluents of food industries, has emerged: once reaching surface and ground waters, such residues can cause serious and unpredictable damages to the aquatic life in general. 2,3 The estimate world production of dyes and pigments is between 750 to 800 thousand tons per year, of which 26 thousand tons are annually consumed in Brazil. 4 About 20% of the world production is lost and dispersed into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…2 In Brazil, the current legislation from the National Health Surveillance Agency (ANVISA, www.anvisa.gov.br) allows the use of only eleven artificial food dyes: Amaranth (CI 16185), Erythrosine (CI 45430), Red 40 (CI 16035), New Coccine (CI 16255), Sunset Yellow (CI 15985), Tartrazine (CI 19140), Indigo Carmine (CI 73015), Brilliant Blue (CI 42090), Carmoisine (CI 14720), Fast Green (CI 42053) and Patent Blue V (CI 42051). 3 Although these synthetic dyes are tolerated, their use can cause some adverse effects. For instance, some studies have shown that dyes can cause simple hives, asthma and immune responses, and even cancer in laboratory animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…: azo, antraquinona, indigóides, etc.) [4][5][6][7] . Cerca de 60% dos corantes utilizados em indústrias têxteis são corantes azos, que se caracterizam pelo grupo -N=N-ligados a sistemas aromáticos 1 , sendo que a função azo inclui os principais tipos de corantes reativos.…”
Section: Introductionunclassified